Challenges and opportunities for mitigation in the agricultural sector - Verchot, Louis V. (2014)
? Agriculture accounts for 10-12% of the total global anthropogenic emissions of GHGs or between 5.1 and 6.1 GtCO2e per annum. Between 1990 and 2010 emissions increased by around 18%, with a greater increase after 2005. ? The technical mitigation potential of agriculture (considering all gases and sources) by 2030 is estimated to be between 4.5 and 6 Gt CO2e yr-1 . The economic potential of all agricultural management practices by 2030 is considerably lower than the technical potential. ? About 30 percent of this potential can be achieved in developed countries and 70 percent in developing countries. ? Agricultural GHG mitigation options are cost competitive with options in other sectors (e.g., energy, transportation, forestry) in achieving long-term (i.e., 2100) climate objectives. ? Similar to other economic sectors, mitigation efforts in agriculture can be adopted in the context of a multilateral international agreement, as part of a development national strategy, or as a voluntary initiative by the private sector.